2015
DOI: 10.1186/s13104-015-1484-2
|View full text |Cite
|
Sign up to set email alerts
|

Peer interviewing in medical education research: experiences and perceptions of student interviewers and interviewees

Abstract: BackgroundInterviewing is one of the main methods used for data collection in qualitative research. This paper explores the use of semi-structured interviews that were conducted by students with other students in a research study looking at cultural diversity in an international medical school. Specifically this paper documents and gives ‘voice’ to the opinions and experiences of interviewees and interviewers (the peers and the communities) on the value of peer interviewing in the study and outlines (1) the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 36 publications
2
42
0
1
Order By: Relevance
“…For this reason, we decided that engaging other medical students to act as interviewers would be less confrontational for participants, enabling them to share possible disturbing emotions and experiences [21]. …”
Section: Methodsmentioning
confidence: 99%
“…For this reason, we decided that engaging other medical students to act as interviewers would be less confrontational for participants, enabling them to share possible disturbing emotions and experiences [21]. …”
Section: Methodsmentioning
confidence: 99%
“…The academic researcher did not have any personal experiences of illness to bring to the interview, but drew on other experiences to develop a sense of "commonness." Without negating the power of shared illness experiences, these findings illustrate the importance of considering similarities and differences at a range of levels 23 and open up for a broader discussion of insider/outsider perspectives in peer interviews.…”
Section: Discussionmentioning
confidence: 81%
“…These differences were supported by the qualitative reading of the interview transcripts which showed that peer interviewers generally inserted more information about themselves into the interviews than the academic researcher, but that the different types of peer interviewers also varied widely in their approach. The academic researcher did not have any personal experiences of illness to bring to the interview, but drew on other experiences to develop a sense of “commonness.” Without negating the power of shared illness experiences, these findings illustrate the importance of considering similarities and differences at a range of levels and open up for a broader discussion of insider/outsider perspectives in peer interviews. As noted by Thomson et al and Greene et al, it is often highly complex to determine what constitutes a “peer,” as peer interviewers may have certain characteristics in common with their interviewees, but may also differ significantly in others.…”
Section: Discussionmentioning
confidence: 82%
“…Byrne et al (2015, p. 7) assert that peer interviewing is beneficial to reduce, although not eradicate, 'power differentials.' Having had the same types of work experiences made it easier to explore and gain a depth of understanding around lived experiences in the interview process (Byrne et al, 2015).…”
Section: Lecturersmentioning
confidence: 99%